Improving oral health in migrant and underserved populations: evaluation of an interactive, community-based oral health education program in Washington state - Ileana Ponce-Gonzalez; Allen Cheadle; Gino Aisenberg; Laura Flores Cantrell (BMC, 2019)
Abstract Objectives Oral health is one of the greatest unmet health needs of migrant farmworkers and many migrant workers lack basic oral health knowledge. This paper presents evaluation results for an oral health education program designed to both increase knowledge concerning oral health practices and to gain a better understanding of the knowledge, attitudes and behaviors regarding oral health among migrant workers. Methods We used a pre-post uncontrolled design to assess the impact of the education program on participant knowledge about oral health practices. Changes in knowledge were assessed using a paper and pencil survey given to participants before the session began (pre) and at the end of the session (post). The pre-post survey was supplemented by qualitative information in the form of participant self-reported barriers and facilitators, and figure drawings illustrating their feelings about the state of their own oral health. Results There were 311 participants in 12 workshops held in 2017 throughout Washington State. There were statistically significant increases in knowledge for all of the pre/post survey questions. Questions with particularly large improvements included: the results of having a mouth infection, factors causing oral health problems, and whether children in low-income families experience more tooth decay. Conclusions An interactive, lay-led oral health education program can be an effective way to increase oral health knowledge in migrant populations. Recommendations for similar programs include using interactive approaches to engage participants, being open to learning and changing your own thinking, and using lay leaders for the education sessions.